The role of cytokines TGF-beta1 and FGF-1 in the expression of characteristic markers of rat liver myofibroblasts cultured in three-dimensional collagen gel - Peterová, Eva; Mrkvicová, Alena; Podmolíková, Lucie; Řezáčová, Martina; Kanta, Jiří (Physiological research, 2016)
Rat liver myofibroblasts (MFB) are the key cells involved in the deposition of extracellular matrix in fibrotic liver. They were isolated by repeated passaging of non-parenchymal cell fraction and cultured in 3-dimensional (3D) collagen gel mimicking tissue. The transfer of MFB from plastic dishes to collagen resulted in the change in their shape from large and spread to slender with long extensions. The expression of transforming growth factor-beta1 (TGF-beta1) and of MFB markers, alpha-smooth muscle actin (alpha-SMA) and cellular fibronectin (EDA-FN), on protein level was significantly decreased in collagen gel. The gel did not change the expression of metalloproteinase MMP-2 but activated the proenzyme. The experiments with inhibitors of metabolic pathways showed that EDA-FN and alpha-SMA were differently regulated. The expression of EDA-FN required functional TGF-beta1 receptors and was also dependent on the activity of protein kinases MEK1 and MEK2. alpha-SMA expression was primarily determined by the 3D environment. Fibroblast growth factor-1 (FGF-1) in combination with heparin decreased the expression of alpha-SMA and increased the expression of EDA-FN in the cells on plastic. The cellular environment may influence the cells per se and may modify the action of other agents.
Keywords: Liver; Animals; matrixová metaloproteinasa 2; biologické markery; játra; Fibronectins; Biomarkers; Transforming Growth Factor beta; dioxoly; transformující růstový faktor beta; Butadienes; kultivované buňky; Rats, Sprague-Dawley; Cells, Cultured; Benzamides; Culture Techniques; Male; myofibroblasty; aktiny; potkani Sprague-Dawley; benzamidy; Actins; nitrily; fibronektiny; Fibroblast Growth Factor 1; fibroblastový růstový faktor 1; Nitriles; Myofibroblasts; Dioxoles; butadieny; kultivační techniky; zvířata; mužské pohlaví; Matrix Metalloproteinase 2